Cyber-Enabled Human Trafficking in Southeast Asia: A New Frontier of Exploitation - Mochamad Kevin Romadhona; Sri Endah Kinasih; Eni Sugiarti; Rachmat Dimas Oktafenanda; Alaa Basil Baqer Alfadhel (IJCLS (Indonesian Journal of Criminal Law Studies), 2026)
Human trafficking in ASEAN has evolved into a hybrid system that combines traditional forms of exploitation with rapidly expanding digital infrastructures. Despite growing attention to trafficking and cybercrime, limited research explains how digital technologies structurally reshape trafficking operations across Southeast Asia. This study addresses this gap by analysing the intersection of trafficking and cyber-enabled crime, focusing on online recruitment, encrypted communication, and digital financial systems. The research employs a qualitative design integrating doctrinal legal analysis, comparative case studies, and socio-digital mapping of trafficking patterns across selected ASEAN countries. It draws on regional legal instruments, national regulations, and documented cross-border cases. The findings reveal that cyber-enabled trafficking accelerates victim recruitment, strengthens transnational coordination, and increases profitability through mechanisms such as scam compounds, livestreamed exploitation, and cryptocurrency-based laundering. At the same time, ASEAN responses remain constrained by fragmented cybercrime laws, limited digital forensic capacity, and weak cross-border cooperation. This study contributes an integrated analytical framework linking legal-institutional gaps with evolving digital practices and offers policy-relevant recommendations, including harmonised cybercrime definitions, enhanced regional data systems, and strengthened investigative collaboration.